Photo-active catalysts in building and construction materials for air pollution treatment: A bibliometric analysis. (2022) - Nema, A.; Kaul, D.S.; Mukherjee, K.; Jeyaraman, J.D.
Abstract: In recent years several studies have been carried out on the integration of photocatalysts in building and construction materials for treatment of air pollutants. The exposure of Ultraviolet–Visible light to photocatalysts make them active to decompose various toxic air pollutants into less toxic or environment friendly products. The synthesis of new photo-catalytic material and their modifications through impregnation could ultimately lead to the technologies for the cost-effective mitigation of environmental problems. In order to understand and assess the current trends on the research activities related to photo-active building materials for pollution treatment, a bibliometric analysis has been carried out in this study. The keywords related to photo-catalysis and building material were used to extract data on research papers from Scopus database. The bibliometric analysis provided window towards understanding the research trend in photocatalytic materials, popular photocatalysts and target contaminants degraded when photocatalysts are impregnated into construction materials. It was found that research is moving towards use of solar light for air pollution treatment. Titania has been considerably modified with metallic and non-metallic dopants to further improve its catalytic activities. New catalyst, several in number (e.g., WO3 decorated ZnO) were also added to the list to promote use of solar light. These different catalysts have been experimented to treat different compounds and were operated under different conditions for the pollution treatment.